International exploration of technology equity and the digital divide : critical, historical and social perspectives - Leigh, Patricia Randolph (Hershey, PA : Information Science Reference, 2011)
"This book explores and presents research that centers on the historical, political, sociological, and economic factors that engender global inequities"--Provided by publisher.
Includes index.
Bibliography: p. 210-230
Keywords: Technological innovations -- Social aspects; Information society; Information technology -- Social aspects